(untitled) (Fiep Bulletin - online, 2016)
This article aims to reflect on the influence of media in the context of the discipline of Physical Education in schools. Aiming to discuss critical perspectives from the concepts and practices of media education as much as the instrumental - didactic approach of using media and games in the discipline; as the educational approach to the media. Since various media content have as themes the physical culture and sport, with a massificadora prospect thereof. Ideologies of such content may influence the daily lives of young people, negatively, as the incessant search for the perfect body and practice / hearing of certain sports that the media offer. Therefore, points to the need to work a critical attitude with students facing such content , contributing to civic education of the same.